Ultra-rare mutations in SRCAP segregate in Caribbean Hispanic families with Alzheimer disease. (October 2017) - Vardarajan, Badri N.; Tosto, Giuseppe; Lefort, Roger; Yu, Lei; Bennett, David A.; De Jager, Philip L.; Barral, Sandra; Reyes-Dumeyer, Dolly; Nagy, Peter L.; Lee, Joseph H.; Cheng, Rong; Medrano, Martin; et al.
Abstract : Objective: To identify rare coding variants segregating with late-onset Alzheimer disease (LOAD) in Caribbean Hispanic families. Methods: Whole-exome sequencing (WES) was completed in 110 individuals from 31 Caribbean Hispanic families without APOE ε4 homozygous carriers. Rare coding mutations segregating in families were subsequently genotyped in additional families and in an independent cohort of Caribbean Hispanic patients and controls. SRCAP messenger RNA (mRNA) expression was assessed in whole blood from mutation carriers with LOAD, noncarriers with LOAD, and healthy elderly controls, and also from autopsied brains in 2 clinical neuropathologic cohort studies of aging and dementia. Results: Ten ultra-rare missense mutations in the Snf2-related CREBBP, activator protein ( SRCAP ), were found in 12 unrelated families. Compared with the frequency in Caribbean Hispanic controls and the Latino population in the Exome Aggregation Consortium, the frequency of SRCAP mutations among Caribbean Hispanic patients with LOAD was significantly enriched ( p = 1.19e-16). mRNA expression of SRCAP in whole blood was significantly lower in mutation carriers with LOAD, while the expression in whole blood and in the brain was significantly higher in nonmutation carriers with LOAD. Brain expression also correlated with clinical and neuropathologic endophenotypes. Conclusions: WES in Caribbean Hispanic families with LOAD revealed ultra-rare missense mutations in SRCAP, a gene expressed in the brain and mutated in Floating-Harbor syndrome. SRCAP is a potent coactivator of the CREB-binding protein and a regulator of DNA damage response involving ATP-dependent chromatin remodeling. We hypothesize that increased expression in LOAD suggests a compensatory mechanism altered in mutation carriers.